2021
DOI: 10.3390/ijms222312801
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Activation in the Dorsal Root Ganglion in Rats Developing Autotomy after Peripheral Nerve Injury

Abstract: Autotomy, self-mutilation of a denervated limb, is common in animals after peripheral nerve injury (PNI) and is a reliable proxy for neuropathic pain in humans. Understanding the occurrence and treatment of autotomy remains challenging. The objective of this study was to investigate the occurrence of autotomy in nude and Wistar rats and evaluate the differences in macrophage activation and fiber sensitization contributing to the understanding of autotomy behavior. Autotomy in nude and Wistar rats was observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Macrophages play important roles in the regulation of immune responses following nerve injury (Chernykh et al, 2016). After peripheral nerve injury, macrophages in ipsilateral DRG rapidly elevate proinflammatory cytokines such as IL‐1β and TNF‐α, which facilitate the sensitization of nociceptive pathway and promote pain development and maintenance (Calvo et al, 2012; Xu et al, 2021). Our results showed that Hk2 ablation effectively reduced the release of proinflammatory cytokines in DRG, as was consistent with the reduced density of macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages play important roles in the regulation of immune responses following nerve injury (Chernykh et al, 2016). After peripheral nerve injury, macrophages in ipsilateral DRG rapidly elevate proinflammatory cytokines such as IL‐1β and TNF‐α, which facilitate the sensitization of nociceptive pathway and promote pain development and maintenance (Calvo et al, 2012; Xu et al, 2021). Our results showed that Hk2 ablation effectively reduced the release of proinflammatory cytokines in DRG, as was consistent with the reduced density of macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Irrigatable nociceptorsare intact hyperexcitable fibres 39 . As a result, the patient may have chronic pain, numbness, or evoked pains.…”
Section: Fig 3: Etiology Symptom and Mechanismmentioning
confidence: 99%
“…On occasions, the definition of autotomy has been further expanded. Primarily, the term was co-opted by several other fields of biological science to describe animals that reproduce asexually through binary fission [ 7 ] or vertebrates that exhibit self-mutilation or denervation following neural degradation [ 8 ]. Because they fall outside the definition of autotomy presented above, these behaviours will not be covered in this review.…”
Section: Introductionmentioning
confidence: 99%